Radiation- Induced Trismus: A Concise Review of Pathogenesis, Prevention and Management - Efsun Somay; Busra Yilmaz; Erkan Topkan; Ahmet Kucuk; Berrin Pehlivan; Ugur Selek (Current Practice in Medical Science Vol. 8, 2022)
Trismus is one of the most difficult-to-treat side effects of anti-cancer treatment for patients with head and neck cancers (HNC). The temporomandibular joint, pterygoid, and temporalis or masseter muscles all have a high risk of causing trismus when exposed to high-dose radiotherapy (RT), namely radiation-induced trismus (RIT). Fibrosis in skeletal muscles, synovial fluid, extracellular matrix, and articular cartilage is considered to occur as a result of RT-induced inflammation and tissue hypoxia mediated by inflammatory mediators, which play key roles in the development of RIT. The most commonly cited risk factors for RIT include genetic factors, age, tobacco and alcohol consumption, poor oral hygiene, tumor localization, tumor size, advanced T-stage, presence of perineural invasion, tumor proximity to the masticatory apparatus, limitation of initial maximum mouth opening, large RT volumes, and high masticatory apparatus doses. RIT can affect as many as 42% of patients after HNC irradiation. The current review aims to discuss the accessible evidence considering the pathogenesis, risk factors, preventive methods, and treatment strategies of RIT, which is a severe late side effect of RT or chemoradiotherapy that reduces the quality of life of affected patients by impairing daily oral functions such as chewing, eating, drinking, and speaking. Furthermore, given the growing body of evidence suggesting that chronic inflammation is one of the major causes of RIT, the current review focuses on the potential role of pre-existing systemic or local inflammation, as well as RT-induced inflammation, as a cause of RIT in HNC patients receiving RT or chemoradiotherapy, which may open a new window for RIT prevention and treatment.